Earned Value Method Evaluation of Project Time and Cost Control on Crane Support Structure Construction Projects PT Pindad (Persero) - Yopi Lutfiansyah; Wilhelmus Tarigan (Journal of World Conference (JWC), 2021)
PT Pindad (Persero) is a manufacturer of heavy-duty equipment such as armoured vehicles. As a result, a crane facility is required to facilitate the material transportation operations, which is supported by a steel structure apart from the building structure. The crane support structure construction process was 19.75 percent delayed until the 12th week. The goals of this study were carried out to evaluate project control using the Earned Value method, which intends to identify project performance in terms of cost and time before and after evaluating project control and knowing the predicted cost and time of total project completion. Schedule Performance Index (SPI) of 0.85 shows a delay of 10.927 percent from the initial plan of 73.731 percent with a realization of 62.804 percent. Meanwhile, the Cost Performance Index (CPI) of 1.22 indicates that the costs incurred are still less than the estimated budget, with a potential profit of Rp. 1,144,245,992.81 or 11,425 percent of the total project budget. Based on the analysis of performance calculations, the estimated project completion time is 26 weeks, or longer than the planned schedule of 22 weeks. In terms of cost, the estimated cost of completing this project is Rp. 8,870,754,007,19. This means that, with the current project cost performance, the project will have a potential profit of Rp. 1,144,245,992.81 or 11,425% of the total project budget. Based on performance calculations, the estimated project completion time is 26 weeks, which is longer than the planned schedule of 22 weeks. The total cost of completing this project is projected to be Rp. 8,870,754,007,19. This means that, regarding the existing project cost performance, the project has a potential profit of Rp. 1,144,245,992.81, or 11.425% of the total project budget.